2018
DOI: 10.3390/nu10070870
|View full text |Cite
|
Sign up to set email alerts
|

In Overweight or Obese Pregnant Women, Maternal Dietary Factors are not Associated with Fetal Growth and Adiposity

Abstract: The aim of our study was to evaluate associations between maternal dietary factors and fetal growth and adiposity in overweight and obese women. Women randomised to the ‘Standard Care’ group of the LIMIT trial were included. Maternal dietary factors including Healthy Eating Index, total energy, fat, carbohydrates, protein, glycaemic load and index were measured using the Harvard semi-quantitative Food Frequency questionnaire at time of study entry, 28 and 36 weeks’ gestation. Fetal ultrasound measurements of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Overall, there was no difference between the intervention group compared to the control group who simply received standard care during pregnancy with respect to children's body mass index (BMI) at 5 years of age. These results are supported by other studies that also intervened on groups of overweight or obese mothers and found no consistent associations between maternal diet and fetal adiposity [54].…”
Section: Nutritional Factors and The Adipose Tissue Programmingsupporting
confidence: 69%
“…Overall, there was no difference between the intervention group compared to the control group who simply received standard care during pregnancy with respect to children's body mass index (BMI) at 5 years of age. These results are supported by other studies that also intervened on groups of overweight or obese mothers and found no consistent associations between maternal diet and fetal adiposity [54].…”
Section: Nutritional Factors and The Adipose Tissue Programmingsupporting
confidence: 69%
“…Epidemiological studies report that the timing of maternal nutrient restriction has a major influence on outcome in terms of predisposing the resulting offspring to adult obesity [ 45 ]. Nevertheless, there are some discussions about this point because some authors do not identify consistent associations between maternal diet and measures of fetal growth and adiposity in overweight and obese women [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A pooled analysis of two cohorts (Project Viva in the USA and the Rhea cohort in Greece) found that adherence to a Mediterranean dietary pattern during mid-pregnancy predicted lower BMI, waist circumference and skinfold thicknesses in offspring across childhood [89]. Yet, a recent study of 721 overweight/obese pregnant women reported no consistent relationship of diet quality indicators, including the HEI, carbohydrate and protein intake and total energy intake, with fetal ultrasound measurements of adiposity at 28-36 weeks' gestation [90]. While the utility of fetal ultrasounds for assessing neonatal adiposity requires validation, these findings suggest the importance of maternal pre-pregnancy weight status beyond that of diet during pregnancy.…”
Section: Dietary Patternsmentioning
confidence: 99%